Analysis of the Advantages and Disadvantages of Using Social Media in Public Relations Practices to Convey Covid-19 Information in Gorontalo Province - Cahyadi Saputra Akasse; Muh Akbar; Arianto Arianto (Research Synergy Foundation, 2021)
Public Relations has an important role in educating and providing understanding to the public in the midst of the COVID-19 pandemic as it is now. In this case, Public Relations acts as an intermediary between the government and the community by conveying policies related to the government's efforts to prevent the spread of COVID-19. This study aims to analyze the advantages and disadvantages of PR strategies in delivering information on COVID-19 using social media, such as: websites, Facebook, Instagram, and YouTube. The method used in this research is descriptive qualitative with a case study approach. Then the withdrawal of research informants using purposive sampling technique, informants consist of people who are directly involved with the delivery of information on covid-19 by Public Relations, with qualitative data collection consisting of depth interviews, participant observation, and documentation. The results of the study show that there are several advantages, namely (1) wide reach and large number of followers, (2) fast information updates, and (3) presenting informative and educative content. The shortcoming in question is that the management of social media is not yet maximal, which is less interactive in responding to public comments through comments on social media. The limitation of this study is that researchers only focus on the PR strategy in delivering information about COVID-19 in Gorontalo Province through social media only and not at the level of other conventional media, namely through websites, Facebook, Instagram, and YouTube. The value and originality of this research is the delivery of information and efforts to prevent the spread of covid-19 which is conveyed through social media PR. The contribution of this research to future PR practices is a deeper implementation of the concept of digital PR, especially during a pandemic like now where everything is done online.